Root Sensitivity and the Possible Treatments with Nanomaterials - Seubbuk Sangkhamanee, Sujiwan; Tansriratanawong, Kallapat (Khon Kaen University Dental Journal, 2021)
Root sensitivity is a common complication that occurs after periodontal therapy. The etiology is multifactorial, which causes the exposure of dentin. The hydrodynamic theory is the underlying mechanism that describes dentin sensitivity. However, the exact mechanism of how root sensitivity occur is still unknown. This review comprises the prevalence, etiology and managements of root sensitivity. The effect of mechanical debridement on the structure of root is also included. Due to the increasing attention in nanotechnology and nanomaterials, the use of nanomaterials in the management of dentin hypersensitivity are reviewed as a part of the management improvement. Finally, the understanding of root sensitivity and the possible applications of nanomaterials in the treatment together with some research questions that may lead to more understanding and more satisfying managements for root sensitivity are discussed.